PERIPHERAL UNILATERAL/ BILATERAL LIMB EDEMA AS AN EARLY WARNING SIGN IN DIABETES MELLITUS- A PROSPECTIVE OBSERVATIONAL STUDY (Journal of Pharmaceutical Negative Results, 2022)
Objective: Lower limb edema is one of the frequently encountered pathological conditions in the clinical scenario and subjected to critical evaluation. Multiple pathologies are involved in the development of limb edema. So the present study was conducted to evaluate peripheral unilateral/ bilateral limb edema an early warning sign in diabetes mellitus. Methods: This was an observational study conducted on 71 patients presented with edema. Using quantitative and qualitative analysis, the cause and prognostic impact of diabetes mellitus in both unilateral and bilateral leg edema as well as in other pathologies were evaluated. Results: In this study the prevalence of edema was 91.5% with majority of the patients (83.1%) with unilateral edema. In patients with edema, diabetes was present in 73.2% of the cases. There was significant association between the presence of edema in diabetes mellitus patients (p=0.02). . Further, there was no significant association in the formation of edema in ulcer, cellulitis, gangrene and filariasis patients (p>0.05). Conclusion: Thus, limb edema is an early warning in diabetes or local diabetic foot diseases. An evaluation and accurate treatment must be followed to prevent morbidity and mortality.